Formy i źródła poezji Aleksandra Galicza - Osiewicz, Bartosz (Wydawnictwo Naukowe UAM, 2016)
This monograph constitutes the first attempt to take a comprehensive look at the poetry of Alexander Arkadievich galich (born ginzburg; 1918–1977) from the perspective of its diversity of forms and sources in Polish studies on Russian literature. It focuses on the Russian phenomenon of author song, which appeared during “the thaw” and was consequently co-created by galich and it was within the framework of this genre that the poet-bard’s illegal lyrical masterpieces were written. The book also emphasizes “the dual nature” of author song, which simultaneously functions as a literary phenomenon and a universal generator of forms. Moreover, particular attention is paid to examining the genologic diversity of galich’s lyrics, full of derived forms of music-poetic genre relations or innovative fusions that emerged from their intermingling with different literary genres. Furthermore, the monograph also offers a look at the singing poet’s artistic word through the prism of intertextuality in order to highlight the multidimensional nature of his lyrics. In revealing the multilevel presence of someone else’s texts in galich’s musical poems and showing that outer constructive elements of his works are characterized by meaningful qualities, the present author aims to prove the existence of a unique and inseparable relation between galich’s author songs and Russian high culture.

Monografia stanowi pierwszą na gruncie polskiego literaturoznawstwa rusycystycznego próbę całościowego spojrzenia na poezję Aleksandra Galicza pod kątem bogactwa jej form i źródeł. W centrum uwagi znajduje się rosyjska pieśń autorska, jako „odwilżowy” nurt poetycki, w ramach którego powstały arcydzieła nielegalnej liryki Galicza. Obiektem obserwacji jest również „podwójna” natura pieśni autorskiej jako zjawiska literackiego i uniwersalnego generatora form. Szczególna uwaga poświęcona jest zbadaniu genologicznej różnorodności liryki Galicza, obfitującej w pochodne muzyczno-poetyckich filiacji gatunkowych oraz nowatorskie fuzje powstałe na bazie wzajemnego przenikania się odmiennych gatunków literackich. Do ukazania wielowymiarowości liryki Galicza przyczynia się także spojrzenie na słowo artystyczne śpiewającego poety przez pryzmat kategorii intertekstualności. Ujawnienie wielopoziomowej obecności „cudzych” tekstów w tkance muzycznych wierszy Galicza oraz wykazanie sensotwórczych właściwości zewnętrznych elementów konstrukcyjnych jego dzieł potwierdza istnienie nierozerwalnego związku pieśni autorskiej pisarza z wysoką kulturą rosyjską.
Forms and sources of Alexander galich’s Poetry
Keywords: Aleksander Galicz; pieśń autorska; gatunek literacki; interteksualność